Enhanced Production and Techno-Economic Analysis of Sustainable Biofuel Production via Continuous Hydrogenation of Furfural Using the Cu-ZnO-Al2O3 Catalyst - Saha, Biswajit; Racha, Arundhathi; Chaudhary, Puneet Kumar; Singh, Brijesh Kumar; Samanta, Chanchal; Newalkar, Bharat L. (ACS Sustainable Chemistry & Engineering, 2025)
2-Methylfuran is a perfect green solution on the pathway of finding alternative fuels. We report here for the first time the continuous production of 2-methylfuran (2-MF), a sustainable biofuel from biomass-derived furfural (FFA), over an industrial Cu-ZnO-Al2O3 (CZA) catalyst. The modified coprecipitation method provides a uniformly dispersed crystalline structure to the synthesized catalysts, along with intended copper (Cu) loading achievement. Different Cu loadings affect the catalytic behavior and activity. Hence, CZA catalysts with two Cu loadings of 9.8 and 4.7% were studied in detail, denoted as C1 and C2, respectively. The catalysts were characterized via XRD, N-2 adsorption, H-2-TPR, NH3-TPD, XPS, ICP-MS, and TEM. Remarkably, the prepared catalysts demonstrate balanced acid sites with mesopores, a high surface area and pore volume, and better controlled nanoparticle size promoting catalytic activity. TEM and H-2-TPR studies reveal a better Cu dispersion. Existence of Cu2+ and Cu (+) even after reduction by XPS study proves the efficiency of the synthesized catalysts. Furthermore, TGA indicates the stability of CZA catalysts. To understand catalytic activity and selectivity, the investigation was carried out in a packed-bed fixed-bed stainless steel reactor. Better physiochemical properties result in high FFA conversion of 33.8% and selectivity of 99.6% for 2-MF. No side products were formed during reaction otherwise improbable via the continuous method. Compared with available literature, the CZA catalyst was found to exhibit superior catalytic performance. The reaction kinetics of furfural hydrogenation to 2-methylfuran was investigated, and it was found that the reaction order is high, and the activation energy was 61.2 kJ/mol. The rate constant k clearly obeyed the Arrhenius law from 180 to 220 degrees C. In addition, evaluation of reaction kinetics also indicated the absence of ring hydrogenation and decarbonylation products, which is difficult to achieve. Finally, the process shows significant economic viability, which resulted in the minimum levelized production cost for 2-methylfuran of 173,068.16 \$/ton with 78.32% overall energy efficiency.
Keywords: 2-methylfuran (2-MF); continuous production; Cu-ZnO-Al2O3; economic viability; furfural; green synthesis